Optimalisasi Bantuan Hukum Demi Terwujudnya Keadilan bagi Rakyat Miskin (Studi Kasus Hak Terdakwa Yang Tidak Mampu dari Segi Ekonomi untuk Memperoleh Bantuan Hukum Terhadap Kejahatan yang Dilakukannya dalam Proses Peradilan Pidana) - Kurniawan, Fadli Nur Wana (Fakultas Hukum Universitas Negeri Semarang, 2020)
The provision of legal aid is one way to achieve justice for the poor that is given by the state as mandated by the constitution. Several regulations regarding legal aid have been issued by the state through laws. However, the facts in society are that the regulations made have not been effectively implemented so that the meaning of justice is biased. The ineffective implementation in providing legal aid in Indonesia is an interesting legal issue to be studied more deeply in order to find out the main problems that cause the ineffectiveness of providing legal aid in Indonesia which will later look for solutions from ideas that become formulations as optimization of legal aid provision in Indonesia. In criminal cases, in order to ensure the fulfillment of the rights of the accused, legal aid can take on the role of a guard to protect the fulfillment of the rights of the accused to avoid arbitrary treatment from irresponsible officers in the criminal justice process. Free legal aid can also be enjoyed by the defendants who cannot afford it. Legal assistance by advocates aims to avoid harming the sense of justice for the accused, and to protect the principle of justice for all regardless of race, skin color, religion, culture, socio-economic, rich/poor, belief, politics, gender, and ideology background.